Pengaruh Gaya Belajar Terhadap Prestasi Belajar Mahasiswa Program Studi Pendidikan Matematika (IAIM NU) Metro - Widyawati, Santi (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
Learning style is one of the factors that allegedly affect the learning achievement (GPA) of Mathematics Education Mathematics Program of Maarif Nahdatul Ulama Institute of Islamic Studies. The purpose of this research is to know "whether there is influence of learning style type (Visual, Auditorial, and kinestetik) to student learning achievement of Mathematics Education Program of Maarif Nahdatul Ulama Islamic Institute of Mathematics”. The type of this research is comparative causal research with 3 × 1 research design. The population in this research is all students of semester IV of Mathematics Education program of Maarif Islamic Institute Nahdatul Ulama Metro academic year 2015/2016. The sample in this study was obtained by using class random technique. The sample in this study consists of 22 students with details of 10 students who have visual learning style, 4 students who have auditorial learning style, and 8 students who have kinesthetic learning style. Instruments used to collect data are questionnaire learning style and transcript of student grades semester IV of Mathematics Education Mathematics course Maarif Nahdatul Ulama Institute of Islamic Studies. Hypothesis testing in this study used a one way variance analysis with unequal cells.The result of this research is the influence of learning style to learning achievement (GPA) of Mathematics Education Mathematics Program of Maarif Nahdatul Ulama Institute of Islamic Studies. Furthermore, after further test using Scheefe 'method, it was found that students with visual learning styles had the same learning achievement with students with auditorial learning style, while both types of learning styles had better learning achievement compared with students with kinesthetic learning style.